2020
DOI: 10.1002/esp.4856
|View full text |Cite
|
Sign up to set email alerts
|

Channel and vegetation recovery from dredging of a large river in the Gulf coastal plain, USA

Abstract: Anthropogenic impacts in large rivers are widely studied, but studies of recovery once a disturbance has stopped are uncommon. This study examines the biogeomorphic recovery of a 40‐km river corridor on the mid‐Apalachicola River, Florida following the cessation of dredging, disposal, and snag removal in 2002. This failed navigation project resulted in vegetation losses (~166 ha between 1941 and 2004), river widening, and increased point bar areas. We used paired sets of imagery for a 10‐year period during the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
29
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 11 publications
(29 citation statements)
references
References 76 publications
0
29
0
Order By: Relevance
“…River bar area reflects hydrologic changes (Hazel et al, 2010;Wiele et al, 1996), a legacy of landscape disturbance, or historical/modern human activities (Jacobson & Gran, 1999;Martin & Pavlowsky, 2011;Mossa & Marks, 2011). Point (Mossa et al, 2020). Examining the entire river for the same period, we found that the sand bar area decreased 18% (Figure 13).…”
Section: Sand Bar Areamentioning
confidence: 75%
See 1 more Smart Citation
“…River bar area reflects hydrologic changes (Hazel et al, 2010;Wiele et al, 1996), a legacy of landscape disturbance, or historical/modern human activities (Jacobson & Gran, 1999;Martin & Pavlowsky, 2011;Mossa & Marks, 2011). Point (Mossa et al, 2020). Examining the entire river for the same period, we found that the sand bar area decreased 18% (Figure 13).…”
Section: Sand Bar Areamentioning
confidence: 75%
“…Therefore, we selected a pair of aerial photos taken at low to medium water level from 2005 (320 m 3 /s) and 2015 (284 m 3 /s), which was at $30th flow percentile. We adopted the sand bar data fromMossa et al (2020) in RM 40 to 64 reach, and digitized sand bars along the rest of the river at a 1:2500 mapping scale for standardized results. We labelled each point bar according to the closest river mile at the middle of the sand bar and paired bars from both years to compare the changes over time after dredging ended.4 | RESULTS4.1 | Thalweg elevation changeSubtracting the 1960 thalweg elevation from the 2010 thalweg elevation, most of the changes are less than a few metres different but some areas show aggradation of 6 m and others show degradation of nearly 10 m. The moving average of 1 river mile of measurements shows that the upper $20 RM, or 30 km, is typically 1-2 m below zero, indicating degradation, and another pronounced dip of similar magnitude below zero is near RM 27 to 33 (Figure9a).…”
mentioning
confidence: 99%
“…In this sense, Mossa et al . (2020) point out that the anthropogenic impact usually covers the entire length of river corridors and, as shown by Corenblit et al . (2020), may shift biogeomorphic system state.…”
Section: Conceptualizing and Quantifying Biogeomorphological Processementioning
confidence: 91%
“…high-mountain and polar environments, deserts, hillslopes, rivers and wetlands, salt marshes and deltas). In this sense, Mossa et al (2020) point out that the anthropogenic impact usually covers the entire length of river corridors and, as shown by Corenblit et al (2020), may shift biogeomorphic system state. Hence, when it comes to NbS in river management, it is essential to understand how human activities may dominate, and may even be considered as a key zoogeomorphic agent, placed within the biogeomorphic systems of the Anthropocene.…”
Section: Conceptualizing and Quantifying Biogeomorphological Processe...mentioning
confidence: 99%
See 1 more Smart Citation